Pengaruh Permainan Balok Angka Terhadap Kemampuan Mengenal Lambang Bilangan Pada Anak Usia Dini - Pascalian Hadi Pradana (LPPM Universitas Pahlawan Tuanku Tambusai, 2016)
This study aimed to investigate the effect of beam numbers game against the ability to know the numbers emblem. This research is a quantitative research, the sample is early childhood, which amounted to 38 children. These samples were selected by purposive area has been chosen based on objective and specific considerations, namely the ability to know the numbers are still minimal emblem. The technique of collecting data through observation, interviews, and documentation. In analyzing this data, as the independent variable (variable x) is playing blocks of numbers, while the dependent variable (variable y) is the ability to know the numbers emblem, used its product moment correlation when the influence of beam numbers game against the ability to know the extent emblem bilangan. Use significant 5%, then the price of table r = 0.320. Whereas, its product moment correlation was 0.487. Furthermore, comparing the count r with r table. It turned out that after the count is greater than r of the r table, then the consequences Ho rejected and Ha diterima. Thus can be seen that the working hypothesis is accepted that There Effect Tile Games Score Against Know Your Ability Symbol Numbers.